Morpho-Physiological and Genomic Evaluation of Juglans Species Reveals Regional Maladaptation to Cold Stress - Ebrahimi, Aziz; Lawson, Shaneka S.; McKenna, James R.; Jacobs, Douglass F. (Frontiers in Plant Science, 2020)
Climate change may have unpredictable effects on the cold hardiness of woody species planted outside of their range of origin. Extreme undulations in temperatures may exacerbate susceptibility to cold stress, thereby interfering with productivity and ecosystem functioning. Juglans L. and their naturally occurring interspecific F1 hybrids, are distributed natively across many temperate regions, and J. regia has been extensively introduced. Cold hardiness, an environmental and genetic factor yet to be evaluated in many native and introduced Juglans species, may be a limiting factor under future climate change and following species introductions. We evaluated cold hardiness of native North American and Eastern Asian Juglans along with J. regia genotypes using field data from the Midwestern United States (Indiana), controlled freezing tests, and genome sequencing with close assessment of Juglans cold hardy genes. Many Juglans species previously screened for cold-hardiness were genotypes derived from the Midwest, California, and Europe. In 2014, despite general climate adaptation, Midwestern winter temperatures of −30°C killed J. regia originating from California; however, naturalized Midwestern J. regia survived and displayed low damage. Hybridization of J. regia with black walnut (J. nigra) and butternut (J. cinerea) produced F1s displaying greater cold tolerance than pure J. regia. Cold hardiness and growth are variable in Midwestern J. regia compared to native Juglans, East Asian Juglans, and F1 hybrids. Phylogeny analyses revealed that J. cinerea sorted with East Asian species using the nuclear genome but with North American species using the organellar genome. Investigation of selected cold hardy genes revealed that J. regia was distinct from other species and exhibited less genetic diversity than native Juglans species Average whole genome heterozygosity and Tajima’s D for cold hardy genes was low within J. regia samples and significantly higher for hybrid as well as J. nigra. We confirmed that molecular and morpho-physiological data were highly correlated and thus can be used effectively to characterize cold hardiness in Juglans species. We conclude that the genetic diversity within local J. regia populations is low and additional germplasm is needed for development of more regionally adapted J. regia varieties.